2020
DOI: 10.1097/mph.0000000000001878
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Disposition of Oncology Patients With Non-neutropenic Fever and Positive Blood Cultures

Abstract: Children with cancer and non-neutropenic fever (NNF) episodes are often treated as outpatients if they appear well. However, a small subset have bloodstream infections (BSIs) and must return for further evaluation. These patients may be directly admitted to inpatient units, whereas others are first evaluated in outpatient settings before admission. The best practice for securing care for patients discovered to have outpatient bacteremia are unclear. To determine outcomes and compare time to antibiotics between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Similar results have been described in a study in pediatric patients with leukemia and solid tumors, which reported on 20% versus 3% of bacteremia in neutropenic and non-neutropenic episodes, respectively [15]. In our analysis, all but one bloodstream infection in non-neutropenic patients were due to a Grampositive pathogen, whereas previous data report on a relevant percentage of Gram-negative pathogens also in the non-neutropenic setting [10][11][12], which might be related to the presence of mucositis and barrier damage of the gut in these patients. Whether biomarkers such as procalcitonin are reliable in distinguishing Gram-positive from Gram-negative infections in pediatric cancer patients need to be evaluated in large clinical trials [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have been described in a study in pediatric patients with leukemia and solid tumors, which reported on 20% versus 3% of bacteremia in neutropenic and non-neutropenic episodes, respectively [15]. In our analysis, all but one bloodstream infection in non-neutropenic patients were due to a Grampositive pathogen, whereas previous data report on a relevant percentage of Gram-negative pathogens also in the non-neutropenic setting [10][11][12], which might be related to the presence of mucositis and barrier damage of the gut in these patients. Whether biomarkers such as procalcitonin are reliable in distinguishing Gram-positive from Gram-negative infections in pediatric cancer patients need to be evaluated in large clinical trials [16].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to well established guidelines in pediatric cancer patients presenting with febrile neutropenia [ 3 , 4 , 5 ], data on infections with onset during a non-neutropenic period are limited in children with cancer [ 8 , 10 , 11 ]. Therefore, it is not surprising that the clinical approach in this setting varies widely across institutions [ 9 ], and the use of fluoroquinolones is controversial [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It refers to the higher prevalence of Klebsiella spp. in neutropenic and, vice versa, CoNS in patients without neutropenia 29–32 . Increased CoNS prevalence in patients without neutropenia may result from frequent CVC usage; however, our definition of BSI may potentially have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…in neutropenic and, vice versa, CoNS in patients without neutropenia. [29][30][31][32] Increased CoNS prevalence in patients without neutropenia may result from frequent CVC usage; however, our definition of BSI may potentially have limitations. The number of positive blood culture sets was used to exclude contaminants; however, it can be challenging to differentiate between actual blood culture contamination and true-positive blood culture when blood culture sets were obtained from the CVC alone (which is in concordance with current guidelines), rather than the peripheral vein.…”
Section: Bacteria (N)mentioning
confidence: 99%
“…Inpatient admissions are common and costly for pediatric oncology patients, 1,2 and are often the result of fever, febrile neutropenia (FN), or suspected infection 3,4 . Yet, the underlying cause of fever in both neutropenic 5–10 and non-neutropenic 11–16 children with cancer often remains unknown with negative blood cultures (BCxs). With mortality rates now as low as 0.6% to 3.0% in pediatric oncology patients hospitalized for FN, 5,7,9 there is a need to identify patients in whom fewer BCx may be safely obtained.…”
mentioning
confidence: 99%